Enhanced piezoelectric performance and thermal stability of alkali niobate-based ceramics. Issue 2 (1st February 2019) - Yang, Weiwei; Li, Peng; Li, Feng; Liu, Xing; Shen, Bo; Zhai, Jiwei
Abstract: In this study, 0.5 wt% MnO2 doped (0.99- x )(K0.5 Na0.5 )(Nb0.965 Sb0.035 )O3 –0.01CaZrO3 - x (Bi0.5 K0.5 )(Hf0.98 Ti0.02 )O3 [abbreviated as (0.99- x )KNNS-0.01CZ- x BKHT, x  = 0.01, 0.02, 0.03, 0.04, 0.05, 0.06] lead-free piezoelectric ceramics were fabricated by traditional solid-state reaction method. The microstructure, phase transformation, electromechanical properties and the thermal stability of the ceramics were systematically studied. Resulting from the R-T phase coexisting, a large piezoelectric coefficient ( d 33 ~ 425 pC/N), planar electromechanical coupling factor ( k p ~ 49%) were achieved in the ceramics with x  = 0.04. Furthermore, the specimens with x  = 0.04 also exhibit excellent temperature stability for d 33 which was manifested by the less than 10% variation of d 33 values when the annealing temperature increase from 25 °C to 100 °C. The good comprehensive properties indicate that MnO2 doped (0.99- x )KNNS-0.01CZ- x BKHT ceramics are promising candidates for practical application to eliminate the Pb-based piezoelectric ceramics from the market.